A study of community-based solid waste production and management at Kampung Bako, Kuching, Sarawak - Rahmah, Biak (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The complexity of issues associated with solid waste makes solid waste management a challenging task. The study of community-based solid waste production and management at Kampung Bako provides an overview of current production of solid waste and its characteristic, involvement of the community in relations to management of solid waste, their social attitude and participation in sponsor related programs The result shows that the community generates an average of 3.52 kg of MSW per day per household. Considering the average household size is 6.84, the rate MSW generation per person is 0.51 kg per day. Based on this rate, the total population in Kampung Bako generated MSW nearly 1.51 tonnes/day or 45 tonnes/month. By weight, the major portion of MSW generated is organic wastes, which is potentially valuable as a composting substrate. The study haft shown that not all recyclable materials in waste stream were recovered. The distribution of MSW composition under the six categories are organic wastes 45.5%, followed by plastics (23.3%), miscellaneous wastes (11.9%), glasses (8.5%), paper (7.1%) and metal (3.7%). The study indicated that a high number of respondents (88.3%) has the right perception towards environment as well as high awareness level on recycling (98.6%) and composting (82.1%), with positive attitude towards waste disposal (80%) and recycling (91%). Approximately 80% of the communities practiced recycling as casual recycler and they understood the purpose of practicing recycling as the mean to conserve the environment. However, their knowledge on how recycling contributed to the environmental conservation is still low. The major constraints to initiate recycling to the 20% nonrecycler are waste storage and recycling facilities.